Nexus Analysis of the English Speaking Club in Finland : exploring the ways to integrate - Korol, Anastasiia (2024)
The current study explores an English Speaking Club in Jyväskylä, a city in central Finland through Nexus Analysis. Instead answering pre-determined research questions, this work is seeking to reveal new unquestioned assumptions existing in the Finnish society in the area of migrants’ integration, adult education and language learning. Therefore this study, conducted from within a problematized social practice – the English speaking club, results into a set of questions that challenge existing order. To conduct the nexus analysis, I followed the three steps: engaging, navigating and change. I placed myself as a volunteer in the English Speaking Club, conducted ethnographic observations over 1,5 years and took 6 semi-structured interviews with the Club participants. Therefore, the dataset consists of field notes, texts of the interviews, photos and artefacts (such as written works or notes of the club participants). The data were analyzed with the tools of Nexus Analysis as well as dialogic analysis. This gave the possibility to connect embodied, material practices with participants’ internal perceptions. Nexus Analysis, as an inductive and holistic mode of inquiry lead to a broad spectrum of new questions, that can be divided into 4 groups. These questions of the first group challenge integration as a concept primarily associated with migrants as an opposition to locals. The second group addresses the questions of pedagogical violence in migrant’s education. The third group raises questions about pedagogical approaches to migrants’ education. Finally, the forth group addresses the questions of raising agency as learning to play an active role in society.